Barriers and facilitators related to healthcare practitioner use of real time prescription monitoring tools in Australia - Hoppe, Dimi; Liu, Chaojie; Khalil, Hanan (Frontiers in Public Health, 2023)
Introduction Real time prescription monitoring tools have been implemented in Australia to address the growing concerns of drug misuse, drug-related mortality and morbidity. The objective of this pilot study is to investigate the barriers and facilitators related to healthcare practitioner use of real time prescription monitoring tools. Methods An online survey was distributed to Australian prescribers and pharmacists who use a real time prescription monitoring tool. Data analysis included descriptive statistics, chi-square tests and multivariate logistic regression analyses. Results A total of 102 questionnaires were analysed. Practitioners mainly agreed that the tool was easy to use (n = 64; 66.7%) and access (n = 56; 57.7%), and the data was easy to interpret (n = 77; 79.4%). Over half agreed that they wanted training to guide clinical actions (n = 52; 55.9%) and clinical guidelines or guidance on what to do with the RTPM findings (n = 51; 54.8%). Prescribers were more likely to report difficulties with workplace access to a computer or the internet (n = 7; 21.2%) compared with pharmacists (n = 6; 9.2%; P = 0.037). Practitioners working in community settings (n = 59; 57.9%; P = 0.022) and those with 1-10 years practice experience (n = 45; 44.2%; P = 0.036) were more likely to want training to guide clinical actions in response to RTPM information. Conclusions This is the first known study to investigate the barriers and facilitators related to practitioner use of RTPM tools in Australia.